The Effect of Job’s Tears (Coix lacryma-jobi L.) Substitution on the Organoleptic Properties of Mung Bean (Vigna radiata L.) Tempeh - Amelinda Nathania Royanto; Febriani Lukitasari; Luthfiyah Nurlaela; Diwyacitta Antya Putri (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Due to Indonesia's present reliance on imported soybeans, indigenous foods are being promoted as a substitute source material for tempeh. Two native food ingredients that might encourage food variety are mung beans and Job's tears seeds. The purpose of this study is to examine how the hedonic quality and degree of liking of mung bean tempeh are affected when Job's tears seeds are replaced and yeast is added. This kind of study uses a 3x2 multiple factorial design experimental approach, substituting 15%, 20%, and 25% of Job's tears seeds and adding 0,05% and 0,10% yeast. The formulation was examined at Surabaya State University's Food Technology Laboratory in Ketintang. A 4-1 scale questionnaire including color, fragrance, taste, and texture was used to administer hedonic quality and preference level assessments to thirty semi-trained panelists. Two-Way ANOVA with a significance threshold (α) of 0.05 and further Tukey HSD or Games-Howell tests based on the homogeneity test findings were used to statistically evaluate the data. The average preference level score was 2,50-3,47, and the average hedonic quality score was 2,47-3,33. The investigation's findings demonstrated that the substitution of Job's tears seeds had an influence on the hedonic quality of color (<0,001) and texture (0,003), but not on the scent and taste, while the addition of yeast and interaction had no effect on any hedonic quality criterion (p > 0,05). The substitution of Job's Tears seeds had an effect on color (0,025), but the addition of yeast had no effect on any of the preference level's parameters (p > 0,05); the interaction of treatments had an effect on color, aroma, and taste, but the Tukey HSD test showed no significant difference; and it had no effect on texture.